INTELLECTUAL CAPITAL DAN NILAI TAMBAH EKONOMI - Ardian Prima Putra; Purwanto Purwanto; Bambang Nur Cahyaningrum (MANAJEMEN DEWANTARA, 2021)
Intellectual capital means asset as valuable power source for firms to increase firm performance. One of performance measured is economic value added (EVA). The study aims to find empirical evidence the role intellectual capital and EVA for Firms listed in Indonesia Stock Exchange. Research Method uses quantitative analysis with SPSS 15. Examining data uses linier Regression Analysis that means examining independent variable to dependent variable. The study provided some findings that intellectual capital influence to EVA. Parsial test showed that VACA and VAHU significant influence to EVA, however STVA can not influence significantly to EVA. The beneficial of research such as developing literature between intellectual capital and EVA, for managing intellectual capital and EVA in public firms.Keywords : Intellectual capital, economic value added, Indonesia Stock Exchange